Epidermolysis Bullosa Acquisita - A Case Report - Feranandes Carol Z; Bhat M Ramesh (Wolters Kluwer Medknow Publications, 2002)
A 50 year old lady presented with multiple pruritic fluid filled lesions all over the body of 5 years duration. Lesions healed with scarring and milia. Immunofluroescence confirmed the diagnosis of epidermolysis bullosa acquisita.